A technology alliance's stability evolution based on a network structure analysis. Issue 3 (3rd July 2018) - Li, Hui; Qu, Shi-you; Scherpereel, Christopher M.
Abstract: The study of technology alliance stability is rare in the literature. Research is especially sparse when exploring a technology alliance' stability based on knowledge networks. We construct a weighted two-mode bipartite affiliation network for a technology alliance consisting of academies, universities and corporations; and using the UCINET algorithms for centrality, consensus, structural hole and connectedness; we measure and analyse the effect of knowledge flow frequency on alliance stability. Our analysis reveals that as the alliance matures: (1) corporations increase in importance and universities' power decreases as the alliance moves from a research focus toward an application focus; (2) central organisations of the alliance lose importance, and the network become more balanced; (3) the network becomes more vulnerable to the removal of organisations (it become less stable); (4) members are more specialised and exhibit less communication. Our research both increases the current theoretical understanding of alliance stability and offers guidance for managerial practice.